ARTIFICIAL INTELLIGENCE AND TERRORISM - ALEMAWO, Komlan; FAWIE , Koboyo (Revue Internationale du Chercheur, 2025)
Abstract The growing integration of artificial intelligence (AI) into counter-terrorism strategies by West African states is a major current challenge. This region, unfortunately marked by persistent threats, could benefit from AI to strengthen its security and stability. Indeed, this technology offers unprecedented prospects, both in terms of prevention and in tactical anti-terrorist operations. However, the use of AI raises complex issues, particularly in ethical and legal terms, due to the risks it entails. It is therefore crucial to reconcile the potential of AI with the challenges it poses, by ensuring a rigorous and responsible framework for its use. One promising avenue would be to promote in-depth research within West African states to develop effective defensive and offensive weapons systems that strictly comply with current ethical and legal standards. In this context, this paper aims to demonstrate that AI could be a decisive strategic asset in strengthening responses to terrorism in West Africa, provided that its use fully respects fundamental rights and freedoms.